IMPACT OFJOB SATISFACTION ON EMPLOYEE PERFORMANCE IN IT INDUSTRY - Yadav Nukanaboina, Dr. Kiran Kumar (The journal of contemporary issues in business and government, 2022)
This research was conducted to investigate the impact of job satisfaction (Communication, Recognition, Work and workplace, Benefits and rewards, Supervisor and management) affect performance of IT employees. The data of this study was quantitative collected through questionnaire from 268 respondents from different IT companies of Bengaluru city. The results of the current study reveal that there is a significant positive relationship between job satisfaction with employee performance. The study also discusses the recommendation for future research.